Archiv von: German American Pioneers Home Page - Brand, Maria (2013)
"The web site GermanAmericanPioneers.org has been developed by Maria and Walter Brand. Maria has gathered an extensive history of the activities of German American Pioneers in the region now known as Silicon Valley (the City of San Jose, CA and the surrounding Santa Clara Valley)."
Original-URL(s): http://www.germanamericanpioneers.org/
Keywords: Deutsche; Siedlung; Amerikaner; Website